Evaluation of some properties of fermented milk beverages that affect the demineralization of dental enamel - Carolina Simonetti Lodi; Kikue Takebayashi Sassaki; Fabian Calixto Fraiz; Alberto Carlos Botazzo Delbem; Cleide Cristina Rodrigues Martinhon (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of this in vitro study was to evaluate the erosive capacity of fermented milk beverages, as well as some of their properties that affect the demineralization of dental enamel (pH, buffering capacity, fluoride, calcium and phosphorus contents). Three different batches of 6 commercial brands of fermented milk beverages were analyzed. pH evaluation was accomplished using a potentiometer. The buffering capacity was measured by adding 1 mol L-1 NaOH. Fluoride concentration was assessed by an ion specific electrode after hexamethyldisiloxane-facilitated diffusion, and calcium and phosphorus concentrations were assessed by a colorimetric test using a spectrophotometer. Sixty specimens of bovine enamel were randomly assigned to 6 groups (n = 10). They were exposed to 4 cycles of demineralization in the fermented milk and remineralization in artificial saliva. Enamel mineral loss was determined by surface microhardness (%SMHC) and profilometric tests. The samples' pH ranged from 3.51 to 3.87; the buffering capacity ranged from 470.8 to 804.2 µl of 1 mol L-1 NaOH; the fluoride concentration ranged from 0.027 to 0.958 µgF/g; the calcium concentration ranged from 0.4788 to 0.8175 mgCa/g; and the phosphorus concentration ranged from 0.2662 to 0.5043 mgP/g. The %SMHC ranged from -41.0 to -29.4. The enamel wear ranged from 0.15 µm to 0.18 µm. In this in vitro study, the fermented milk beverages did not promote erosion of the dental enamel, but rather only a superficial mineral loss.